The Influence Of Electronic Marketplace Marketing, Online Customer Review, And Live Streaming On The Decision To Purchase Ventela Shoes Product In Nusantara PGRI Kediri University Students - Putri, Tri Subekti Mei Kusumaning; Puspasari, Ismayantika Dyah (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: This study aims to test and analyze the effects of Marketplace Marketing, Online Consumer Review, and Live Streaming on Consumer Purchasing Decisions through the Shopee Marketplace. Design/Methode/Approach: This research is a type of quantitative causality research with an associative causality approach. The sampling technique uses the accidental sampling method. The population of this research is all active students of Nusantara PGRI Kediri University, with a sample of 40 respondents. This research was conducted using a survey method on Active Students of Nusantara PGRI Kediri University who had purchased Ventela shoe products from the Shopee marketplace. The sampling technique uses data analysis techniques using multiple linear regression tests, coefficient of determination, and t (partial) and F (simultaneous) hypothesis tests. Research Finding: The results of this research prove that the variables Marketplace Marketing, Online Customer Review, and Live Streaming simultaneously and partially have a significant influence on the decision to purchase Ventela shoe products through the Shopee Marketplace among active students at Nusantara PGRI Kediri University. Of the three independent variables, the one that has the most influence on the dependent variable is the live streaming variable with a coefficient of determination value of 0.737.